2012
DOI: 10.1159/000338317
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Discriminant Analysis Using Nuclear Three-Dimensional Analysis in Atypical Cells Prepared from Bronchial Brushing Cytology Cases That Are Cytologically Challenging

Abstract: Objective: Since well-differentiated adenocarcinoma cells of the lung (G1 cancer cells) show mild atypia, their differentiation from benign columnar epithelial cells (benign cells) is often difficult based on morphology. We performed discriminant analysis to distinguish benign from malignant cells by measuring 3-dimensional (3D) changes in nuclear luminance. Study Design: Discriminant analysis of 231 atypical cells prepared by bronchial brushing cytology, which were difficult to morphologically classify as ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Washiya et al sought to discriminate normal columnar cells from adenocarcinoma cells of the lung using the difference of signal intensity relative to the position of the cross section through the nucleus. 11 This study reported that calculation of signal intensity relative to cross sections of the nucleus was useful for distinguishing normal columnar cells from adenocarcinoma cells of the lung. This suggests that the direction of nuclear observation is important during signal intensity extraction for discriminant analysis.…”
Section: Ishii Et Al Conducted Papanicolaou Staining Of Ec Cells Vs mentioning
confidence: 99%
See 1 more Smart Citation
“…Washiya et al sought to discriminate normal columnar cells from adenocarcinoma cells of the lung using the difference of signal intensity relative to the position of the cross section through the nucleus. 11 This study reported that calculation of signal intensity relative to cross sections of the nucleus was useful for distinguishing normal columnar cells from adenocarcinoma cells of the lung. This suggests that the direction of nuclear observation is important during signal intensity extraction for discriminant analysis.…”
Section: Ishii Et Al Conducted Papanicolaou Staining Of Ec Cells Vs mentioning
confidence: 99%
“…We therefore calculated the signal intensity in heterochromatin and euchromatin regions of the nucleus from both the luminal and the lateral faces and determined whether there was a difference in signal intensity. Washiya et al sought to discriminate normal columnar cells from adenocarcinoma cells of the lung using the difference of signal intensity relative to the position of the cross section through the nucleus . This study reported that calculation of signal intensity relative to cross sections of the nucleus was useful for distinguishing normal columnar cells from adenocarcinoma cells of the lung.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on the 3-dimensional structures of nuclei in cell smear specimens and reported objective discrimination using 3-dimensional and discriminant analyses of nuclei [4][5][6] . The nuclei of ASC-US cases in initial cytology were 3-dimensionally analyzed using liquid-based cytology (LBC) specimens prepared by the ThinPrep method.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on the 3-dimensional structures of nuclei in cell smear specimens to investigate the objective discrimination of malignancy using the 3-dimensional analysis of nuclear luminance [15,16,17,18]. Individual nuclei in cell specimens were 3-dimensionally photographed for retrospective discrimination based on Mahalanobis distance using various parameters including pixel counts (area), number of focus layers (number of images with the nuclei microscopically and morphologically focused) and 3-dimensional variation in the coefficient of variation of nuclear luminance between the focus layers (3D-CV), facilitating a discriminant diagnosis between MM and RM [18].…”
Section: Introductionmentioning
confidence: 99%